Análise dos fatores que influenciam a satisfação no trabalho em uma rede de supermercados na fronteira oeste do Rio Grande do Sul - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The employee satisfaction is a key response to the company, making it an important object of study, may influence positively or negatively on the organization. All modern companies try to understand the satisfaction of their employees in order to reverse this at lowering costs, since a company with unhappy employees tend to have a high level of turnover, absence and rumors that can spoil the organization's image. This study aims to identify the level of satisfaction of the employees of a supermarket chain located on the western border of Rio Grande do Sul. The methodology used was a descriptive study with a quantitative and qualitative approach, through questionnaires in the operational area of the company (packagers, cashiers, stockers and clerks). Among the results, we found out that the obtained data revealed that employees are satisfied, but there are specific variables to be worked, such as salaries and promotions that may result in a greater feedback.
Keywords: Satisfação; Liderança; Cultura organizacional; Motivação; Organização; Satisfaction; Leadership; Organizational culture; Motivation; Organization; CNPQ::CIENCIAS SOCIAIS APLICADAS